Guidelines to Create Production Oriented Enterprise for Community Enterprises in the Industrial Sector - Bunsin, Orapin (WMS Journal of Management, 2016)
The article has 2 objectives 1.To study the creation of intellectual capital and creative production for entrepreneur community enterprises in the industrial sector. 2.For propose guidelines to create production oriented enterprise for community enterprises in the industrial sector is appropriate and has the potential to increase productivity. This study used qualitative research methods (Qualitative Research) Individual in-depth interviews individually (In-depth Interview) Sample group, President of community enterprise were 30 of 45 people to cooperate to collect sample. Accounted for 67 percent of the total population. The results revealed that leader enterprise community should be create awareness of intellectual capital. Include 1. Cost of innovation by using ability invest to create products and new services that create added value occur by extension from the original to something new. 2. Capital abilities inherent in people. The ability of each person fit the work to produce creative. 3. Relationships capital with stakeholders by creating a network with outsiders. 4. Capital investments by sources of funds from various sources be used to fit the job. 5. Capital structure organization and job rotation assignments to the group members.6.Capital resource management by using existing resources in the community to produce the maximum benefit. 7. Intangible Cultural Capital The use of unique or outstanding characteristics of each community to build brand awareness with consumers. The creative productivity issues, Should be focus on the process to create innovative products the attention process of production. To achieve the target group's work and member satisfaction contribute to the future leading to revenue growth. Moreover it should be focus increase of value to products and intellectual property.